Analisis Perbandingan Kinerja Keuangan PT. Samudera Indonesia Tbk Sebelum & Sesudah Akuisisi - Tinika, Angelina Siska (Universitas Darwan Ali, 2023)
This study aims to analyze the financial performance before and after the acquisition using financial ratios at PT. Samudera Indonesia Tbk. Financial performance in this study was measured using financial ratios, namely Current Ratio (CR), Debt to Equity Ratio (DER) and Earning per Share (EPS). The method of measuring financial performance uses the Wilcoxon rank sum test. The population in this study is the financial statements of PT. Samudera Indonesia Tbk. The sample used in this study was 2 years before the acquisition and 1 year after the acquisition from 2019 to 2021. The results showed that there was no difference in Debt to Equity Ratio (DER) before the acquisition, while there was a difference in Current Ratio (CR) and and Earning Per Share (EPS) after acquisition.